Perceived social and built environment associations of leisure-time physical activity among adults in Sri Lanka - Shreenika De Silva Weliange; Madhawa Perera; Jagath Gunatilake (BMC Research Notes, 2021)
Abstract Objective Although perceived neighbourhood environment is considered a predictor of leisure-time physical activity (LTPA), evidence for this is limited in South Asia. Thus, the aim was to determine the association between neighbourhood social and built environment features in carrying out LTPA among adults in Colombo District, Sri Lanka. A cross-sectional study among 1320 adults was carried out using validated questionnaires for physical activity (PA) and built environment data collection. Multiple logistic regression analysis was conducted to assess the associations between environment characteristics and LTPA after adjusting for gender, age, employment status, income level and sector of residence. Results A total of 21.7% of adults participated in some LTPA. The commonest type of LTPA was walking; carried out by 14.5%. Moderate and vigorous activity at leisure was carried out by 10.3% and 3.9% respectively. Perceived social acceptance for PA was positively associated with LTPA. Out of the built environment characteristics perceived infrastructure for walking, and recreational facilities for PA were negatively associated with LTPA. Self-efficacy emerged as an important positive correlate of LTPA. The participants were positively influenced by the self-efficacy and perceived social environment which should be addressed when promoting LTPA.